Long- and short-term variability of Arctic sea-ice cover during the Last Interglacial and Marine Isotope Stage 11c - Brian R. Crow; Matthias Prange (Communications Earth & Environment)
Abstract Sea-ice-free Arctic summers are expected within the next decades due to anthropogenic warming. Studying past warm interglacials offers valuable insights into the Arctic climate system under similar conditions. Here we present a series of simulations that represent a chronological sequence of interglacial climate states over Marine Isotope Stages 5e and 11c using the Community Earth System Model. While previous studies attempted to explain the Arctic sea-ice evolution through changes in summer solstice insolation, we demonstrate that summer sea-ice area during both interglacial periods is primarily driven by an inverse relationship with integrated summer energy. Although proxy data yield conflicting results on Last Interglacial Arctic sea-ice cover, our simulations suggest seasonally ice-free conditions across the Arctic during the early interglacial phase. In both interglacials, climate states with intermediate levels of summer sea-ice area are characterized by maximum interannual variability in sea-ice area.